HUBUNGAN ANTARA DAYA LEDAK OTOT LENGAN, KOORDINASI MATA-TANGAN, DAN MOTIVASI BERPRESTASI DENGAN KETERAMPILAN SMASH ATLET BULUTANGKIS U15 - Amar, Ibnu Yunshor; Samsudin, Samsudin; Subandi, Oman Unju (Universitas Hamzanwadi, 2025)
This study aims to analyze the relationship between arm muscle power, eye-hand coordination, and achievement motivation with the smash skills of U15 badminton athletes. The method used is quantitative with a correlational design. The sample consisted of 40 athletes from PB Jaya Raya Ragunan, which were taken using total sampling. Data were collected using a Chronojump Linear Encoder for explosive strength, a modified alternate hand wall toss test for coordination, an achievement motivation questionnaire, and a PBSI smash skill test. The results showed a positive and significant individual relationship between arm muscle explosive power (r=0.741), hand-eye coordination (r=0.735), and achievement motivation (r=0.455) with smash skills. Multiple regression analysis revealed a much stronger simultaneous relationship, with a multiple correlation coefficient (R) of 0.883. The three variables together explained 77.9% of the variance in smash skills (R²=0.779), indicating a strong synergistic effect when the three components were developed in an integrated manner. In conclusion, effective coaching of U15 athletes requires a holistic approach that systematically integrates explosive power training, coordination, and achievement motivation reinforcement to optimize smash skills as a competitive foundation at higher levels.